Electromagnetic Functionalization of Wide‐Bandgap Dielectric Oxides by Boron Interstitial Doping. Issue 39 (21st August 2018) - Park, Dae‐Sung; Rees, Gregory J.; Wang, Haiyuan; Rata, Diana; Morris, Andrew J.; Maznichenko, Igor V.; Ostanin, Sergey; Bhatnagar, Akash; Choi, Chel‐Jong; Jónsson, Ragnar D. B.; Kaufmann, Kai; Kashtiban, Reza; et al.
Abstract: A surge in interest of oxide‐based materials is testimony for their potential utility in a wide array of device applications and offers a fascinating landscape for tuning the functional properties through a variety of physical and chemical parameters. In particular, selective electronic/defect doping has been demonstrated to be vital in tailoring novel functionalities, not existing in the bulk host oxides. Here, an extraordinary interstitial doping effect is demonstrated centered around a light element, boron (B). The host matrix is a novel composite system, made from discrete bulk LaAlO3 :LaBO3 compounds. The findings show a spontaneous ordering of the interstitial B cations within the host LaAlO3 lattices, and subsequent spin‐polarized charge injection into the neighboring cations. This leads to a series of remarkable cation‐dominated electrical switching and high‐temperature ferromagnetism. Hence, the induced interstitial doping serves to transform a nonmagnetic insulating bulk oxide into a ferromagnetic ionic–electronic conductor. This unique interstitial B doping effect upon its control is proposed to be as a general route for extracting/modifying multifunctional properties in bulk oxides utilized in energy and spin‐based applications. Abstract : An extraordinary interstitial doping effect is centered around boron doping in a LaAlO3 :LaBO3 composite, transforming a non‐magnetic insulating oxide into a high‐temperature ferromagnetic conductor. Ionic–electronic interactions of mobile boron interstitial with the host cations and its associated spin‐polarized charge injection tailor both the conductivity and magnetization of the composites, which is a pathway for extracting multifunctional properties in dielectric oxides.